Health equity follows racial equity: learning the impact of historic racism through a summer reading assignment in a graduate public health course - Donna J. Petersen (Frontiers in Public Health)
Prior to a fall semester graduate course in public health, students are encouraged to complete a summer reading assignment based on a book chosen from a curated list of popular literature relevant to public health concepts. From 2020 to 2024, this assignment enabled students to explore the history of structural and systemic racism in the United States and its impacts on current public health policy and programs. Themes from these books are woven into class discussions and further explored in subsequent course assignments. This paper describes the assignment and shares responses from the 1,141 students who completed the reading assignment as well as responses to subsequent assignments completed by the 1,464 students enrolled in the course. Scaffolding of complex and for some students challenging subjects facilitates a deeper understanding of factors critical to understanding contemporary public health challenges and helps students appreciate the significance of the social economic, and political determinants of health, including racism.